Decentralisation and local governance in Nigeria - Tobi, Andrew Ariyo; Ayodeji, Gafar Idowu (Faculty of Administrative Science and Policy Studies, 2023)
Nigeria has over the years, initiated and implemented decentralisation policies to promote effective governance at the sub-national level. However, the narratives on grassroots governance in Nigeria showed that governance at the grassroots has not been effective. This study probed decentralisation in Nigeria to explain its failure to transform governance at the grassroots level. The study utilised a qualitative research approach and relied on information obtained from official publications, textbooks, journals and newspapers, and adopted the vertical and horizontal decentralisation as framework of analysis. The study found that series of efforts aimed at strengthening local governance in Nigeria through decentralisation found expression in the various reforms of the local government system. It found that vertical decentralisation while transferring powers to local government retained supervisory control with the other higher tiers of government. The study further showed that horizontal decentralisation, which ought to focus on empowering community-based organisations, the private sector and civil society is grossly deficient. The deficit of horizontal decentralisation has manifested in the limited impact of non-state actors on governance at the sub-national level. The study recommended a redefinition of vertical decentralisation to reverse the existing central-local relations, which have engendered a top-bottom governance structure and stymied grassroots governance. It further recommended strengthening horizontal decentralisation to encourage the growth and participation of non-state actors in governance at the sub-national level.